The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14393/bj-v34n3a2018-36771
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effect of aqueous extracts of different organs of three sunflower cultivars on germination of radish

Abstract: This study aimed to evaluate the allelopathic potential of aqueous extracts of different organs of three sunflower cultivars on the germination and initial development of radish. The study was conducted in a Laboratory of Plant Physiology of the Federal University of Santa Maria, Brazil. The design was completely randomized in a threefactor scheme with four replications. The first factor consisted of three sunflower cultivars: Olisun 3, Olisun 5, and Aguará 6. The second factor consisted of different organs: l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In comparison with L+S extract, the highest stimulating effect on SG had H and R extracts from both UDP and FDP. Our experimental findings are in line with previous results [12,16,18], which indicate differences of the allelopathic effect among plant parts. These results are contrary to the study of Bashir et al [11], wherein sunflower organ extracts inhibited wheat SG.…”
Section: Effects Of the Aqueous Extracts Of Sunflower On Pea Sgsupporting
confidence: 93%
See 4 more Smart Citations
“…In comparison with L+S extract, the highest stimulating effect on SG had H and R extracts from both UDP and FDP. Our experimental findings are in line with previous results [12,16,18], which indicate differences of the allelopathic effect among plant parts. These results are contrary to the study of Bashir et al [11], wherein sunflower organ extracts inhibited wheat SG.…”
Section: Effects Of the Aqueous Extracts Of Sunflower On Pea Sgsupporting
confidence: 93%
“…H extract showed the highest promotion effect on these indices. Our experiment corroborates with previous results [12,16,20], in which it was found that allelopathic potential of sunflower parts vary from each other. Kandhro et al [25] reported that shoot of sunflower was found more allelopathic than root.…”
Section: Effects Of the Aqueous Extracts Of Sunflower On Pea Agdm And...supporting
confidence: 93%
See 3 more Smart Citations